Strategi Komunikasi Pemasaran Vapor Sindikat Bekasi Dalam Menarik Minat Konsumen - Alfi Akbar Sasra; Mayasari Mayasari; Eka Yusup (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study discusses the communication strategy carried out by Vapor Sindikat Bekasi in increasing consumer buying interest. The theory used is Marketing Mix Communication which has four dimensions, namely product, price, promotion and place. This study used descriptive qualitative method. The data sources in this study are primary and secondary which are obtained through triangulation, interview, observation and documentation data collection techniques which are then analyzed using the Miles and Huberman model data analysis concept which consists of three stages including, data reduction, data presentation and conclusion drawing. . The results and discussion of the research show that the products sold by Vapor Sindikat Bekasi are very good in terms of quality but the packaging is less attractive and the services provided by Vapor Sindikat Bekasi employees are said to be very good and able to provide education to consumers about vaping. The price applied by Vapor Sindikat Bekasi is still the same as that set by similar stores, but Vapor Sindikat Bekasi is superior in terms of providing free goods from several products being marketed. Promotions carried out by Vapor Sindikat Bekasi in increasing consumer buying interest using Instagram social media, also providing promotions and prizes or giveaways on every big day. The place for buying and selling Vapor Syndikat Bekasi with consumers is an area that is easily accessible by all types of private vehicles, making it easier for consumers to communicate with Vaporista Sindikat Bekasi.